Sosialisasi Pelaksanaan SP2TP Menggunaan Pieces di Puskesmas Lubuk Buaya - Linda Handayuni; Hendra Nusa Putra (Jurnal Surya Medika (JSM), 2021)
The Community Health Center hereinafter referred to as the Puskesmas, is a health service facility that organizes public health efforts and first-rate individual efforts, prioritizing promotive and preventive efforts. The recording and reporting system (SP2TP) is a comprehensive and integrated recording and reporting activity for Puskesmas with the concept of puskesmas working areas. PIECES include Performance, Information, Economic, Control, Efficiency, and Service. Puskesmas Lubuk Buaya already uses the e-Puskesmas application and already has PIECES, but it is not yet perfect in its application. This community service's purpose is that the implementation of SP2TP by using PIECES is better at the Lubuk Buaya Health Center. The method used with Research Development. Medical record officers' performance on the implementation of e-puskesmas has been running well on the information is still not accurate in providing information. The economy is still lacking facilities and infrastructure in the smooth implementation of e-puskesmas. There are still errors in the data in control so that supervision is still not guaranteed; efficiency has not been found to increase efficiency in the performance of health centers and services there are still processes that have not been implemented. In the implementation of SP2TP using PECES, it should be optimized so that errors do not occur in the information available at the Puskesmas, and other fields related to reporting will be easier to monitor, including external parties.